The Design of Interactive Mine Forecasting System to Improve Mine Planning Performance - Sugita, I Nengah; Hanafi, Muhammad (The Indonesian Journal of Business Administration, 2019)
Abstract - The objective of this research is to improve the mine planning performance in PT Freeport Indonesia (PTFI). Currently metal forecasting often faces many scenarios and changes shortly because of some dynamic parameters and conditions. The new improved mine planning must be more powerful to handle it. To achieve the objective, the writer surveyed and analyzed the forecasting performance data in the past and then proceeded with a mapping of forecasting process to see how the parameters linked and conditions applied. The team observed that the current conventional method is too rigid for doing mine-mill model simulation. Adjusting the amount of ore delivery to mill needs extension until the Mine Scheduling or Sequencing, beyond than Cutoff grade adjustment. Furthermore, the geological type of ore mined needs fully integration to the mill-model. After the problem identified, by using the Goldratt’s analyses tool called Current Realty Tree (CRT), a team is constructed to analyze some undesired effects and then to seek its solution. Surveying some literatures and benchmarking to other mining companies are conducted to gain more tactical solutions.Finally, a new mine planning method were set up. It uses mining reserve database, filtering concept and bench percentage mining logical formula. This new method is well accepted and implemented to analyze mining scenario quickly. This new method is now applied side by side with convectional method.  This new design is available to produce a robust plan to support strategic planning group on optimizing the strategic mine planning goals. Keywords: Grasberg Surface Mine, Long Range Mine Planning, Forecasting, Mine Scheduling, Interactive Mine Planning.